Actions to influence the care network of home-dwelling elderly people: a qualitative study - Kemper-Koebrugge, Wendy; Wensing, Michel (Health and social care in the community, 2019)
Positive impact of care networks of home‐dwelling elderly people may be based on several network mechanisms: navigation to resources, negotiation between participants and contagion of behaviours. Little is known about actions of participants—elderly people, informal caregivers or formal care providers—to activate such mechanisms and generate support. Aim of this study was to identify actions in relation to these network mechanisms. A cross‐sectional qualitative study of 48 interviews with home‐dwelling elderly people, informal caregivers and formal care providers in the eastern parts of the Netherlands was conducted between March and September 2016. A framework analysis on network mechanisms categorised actions. Actions were reviewed by network party and compared between networks to explore relations between actions and networks. Results showed that participants navigated through existing relations to seek support. Actions on negotiation were aimed at ameliorating existing relations. Few examples and no actions on contagion of behaviours were found. Actions seemed driven by incidents and existing relations. Elderly people rarely initiated actions, informal caregivers felt hampered by their position in the network. Consistent patterns of relations between actions and network characteristics did not emerge. We concluded that the full potential of network‐based support of elderly people is probably underused. Particularly promising seem: navigating the neighbourhood for new informal care, using opposite opinions as a catalyst for change and bringing quality of life and dilemma's into dialogue in the network.
First published: 13 January 2019
Gesehen am 02.10.2019